FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN LOW BACK PAIN (LBP) PADA PEKERJA BATIK DI KECAMATAN PELAYANGAN KOTA JAMBI - Ratu trinita (Jurnal Penelitian Kesmasy, 2026)
Low Back Pain (LBP) is a musculoskeletal complaint frequently experienced by workers in the informal sector, such as batik workers, due to their work activities. The purpose of this study was to determine factors associated with low back pain (LBP) among batik workers in the Pelayangan sub-district, Jambi City. This study used a quantitative analytical observational design with a cross-sectional approach. The study population included all 43 batik workers in Pelayangan sub-district (pattern writing, batik canting, stamping, dyeing, nembok, and pelorotan). Data collection was conducted using questionnaires, fingertip pulse oximetry, and Rapid Upper Limb Assessment (RULA). Data analysis used the chi-square test. The study showed a prevalence of low back pain (LBP) among batik workers of 76.7%. The statistical test results showed that all variables were <0.05. Age (P=0.004), length of service (p=0.001), work duration (p=0.002), movement repetition (P=0.036), work posture (p=0.044), workload (p=0.007), BMI (P=0.043). There is a relationship between age, length of service, work duration, movement repetition, work posture, workload, and BMI with low back pain (LBP) among batik workers in Pelayangan District, Jambi City.